THE EFFECT OF CPAP ON HYPERTENSION IN PATIENTS WITH OBSTRUCTIVE SLEEP APNEA: A LITERATURE REVIEW - Sylwia Wiktoria Kolano; Maksym Sikora; Jakub Nowak; Michael Platschek; Klaudia Dybalska; Julia Kosmulska; Mateusz Kęska; Anna Barbara Tuleja; Michał Drabik; Karol Józef Szkarłat (International Journal of Innovative Technologies in Social Science, 2025)
Obstructive sleep apnea (OSA) is a chronic condition characterized by recurrent episodes of upper airway obstruction during sleep, leading to intermittent hypoxia, sympathetic nervous system activation, and blood pressure dysregulation. Numerous studies have confirmed the frequent coexistence of OSA and hypertension, making this association a significant clinical and public health concern. The aim of this review was to assess the effect of CPAP (Continuous Positive Airway Pressure) therapy on blood pressure in different groups of patients with obstructive sleep apnea, based on current scientific data. The review included publications from 2015 to 2025, available in the PubMed database, regarding randomized controlled trials and meta-analyses assessing the effect of CPAP on blood pressure. A total of 15 randomized controlled trials and meta-analyses were included in the analysis. CPAP therapy remains the gold standard for OSA treatment and can be an effective adjunct to blood pressure control, particularly in patients with resistant hypertension. However, treatment effectiveness depends on adherence to recommendations and appropriate patient selection. Further research should focus on assessing the long-term effects of CPAP, identifying patient phenotypes that best respond to therapy, and developing treatment strategies in combination with antihypertensive pharmacotherapy.